Measurement of electron density in atmospheric pressure argon glow discharge - Tyata, R.B.; Subedi, D.P. (Journal of Science and Engineering, 2014)
In this report, an atmospheric pressure glow discharge (APGD) in argon has been invest igated by means of electrical measurement using parallel plate electrodes. The discharge was produced by passing argon gas at controlled f low rate of 1 lit/min, with dielectric barrier of glass between the electrodes. The inter -electrode spacing was varied from 1 mm to 3 mm. The electrical measurement of the discharge showed that there exists only one current pulse per half cycle in the current waveform indicating the formation of glow discharge. Power balance method was applied for the determinat ion of electron density. Our results showed that the electron density in the discharge is of the order of 1010 cm−3 with 26 kHz frequency of high voltage power supply.